Low-temperature silver paste FPC conductive film for electronic cigarette and preparation method thereof
Patent Information
- Application Number
- CN202511919199.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-18
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2045-12-18
AI Technical Summary
Existing electronic cigarette FPC conductive films are prone to substrate deformation and increased brittleness of conductive circuits during high-temperature silver paste curing. Furthermore, traditional silver paste contains lead, which is not environmentally friendly and affects the dimensional stability and reliability of FPCs.
The low-temperature silver paste FPC conductive film is formed by optimizing the low-temperature silver paste formulation and multi-layer composite structure design, including a substrate layer, an insulating dielectric layer, a conductive circuit layer and a protective layer. It uses materials such as nano-silver particles, lead-free glass powder and organic carriers, and is cured at low temperature to form a continuous conductive network.
It effectively avoids thermal damage to the substrate, improves conductivity and interfacial bonding, enhances bending resistance and environmental friendliness, and extends the service life of core components of electronic cigarettes.
Smart Images

Figure CN121617708B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of flexible electronic device technology, and in particular to a low-temperature silver paste FPC conductive film for electronic cigarettes and its preparation method. Background Technology
[0002] As a new type of tobacco product, electronic cigarettes have core components such as heating elements, airflow sensors, and control circuit boards. These components need to be electrically connected through flexible printed circuit boards (FPCs). The conductive film of the FPC, as a key carrier for signal transmission and energy supply inside the electronic cigarette, needs to meet requirements such as high temperature resistance, bending resistance, excellent conductivity, and strong adhesion to the substrate.
[0003] Currently, most conductive films for electronic cigarette FPCs are prepared using traditional high-temperature silver paste. However, the substrates for electronic cigarette FPCs are mostly polyimide (PI) or polyester (PET) films. The high temperature during silver paste curing can easily cause the PI substrate to shrink and deform, and the PET substrate to soften and melt, affecting the dimensional stability and reliability of the FPC. At the same time, traditional silver pastes have a high glass powder content, which can easily lead to increased brittleness of the conductive circuits and poor bending resistance. Furthermore, some high-temperature silver pastes contain lead glass powder, which does not meet environmental protection standards. Therefore, this invention proposes a low-temperature silver paste FPC conductive film for electronic cigarettes and its preparation method to solve the problems existing in the prior art. Summary of the Invention
[0004] To address the aforementioned problems, the present invention aims to provide a low-temperature silver paste FPC conductive film for electronic cigarettes and its preparation method. This low-temperature silver paste FPC conductive film and its preparation method for electronic cigarettes achieve low-temperature curing and molding by optimizing the low-temperature silver paste formulation and multilayer composite structure design, thus solving the problems of thermal damage, high energy consumption, and low yield of electronic cigarette FPC substrates caused by traditional high-temperature silver paste.
[0005] To achieve the objectives of this invention, the invention is implemented through the following technical solution: a low-temperature silver paste FPC conductive film for electronic cigarettes, comprising a substrate layer, an insulating dielectric layer, a conductive circuit layer, and a protective layer arranged sequentially from bottom to top. The conductive circuit layer is formed by curing low-temperature silver paste. The low-temperature silver paste is prepared by mixing nano-silver particles, glass powder, organic carrier, and functional additives in a mass percentage ratio of 60%-80%:5%-15%:10%-25%:0.1%-3%. The organic carrier is obtained by mixing resin, solvent, and dispersant in a mass percentage ratio of 30%-50%:40%-60%:1%-5%. The functional additives are one or more of coupling agents, antioxidants, and leveling agents.
[0006] A further improvement is made in that: the substrate layer is one of polyimide film and polyester film, with a thickness of 12.5μm-50μm; the insulating dielectric layer is one of epoxy resin coating and polyimide coating, with a thickness of 5μm-20μm; the conductive circuit layer has a line width of 50μm-500μm and a line spacing of 50μm-300μm; and the protective layer is a UV-cured acrylate coating with a thickness of 3μm-10μm.
[0007] A further improvement is that the average particle size of the silver nanoparticles is 50nm-200nm, and the surface is modified with a modifier containing 0.5%-2% of the mass of the silver particles. The modifier is either citric acid or polyvinylpyrrolidone. The specific surface area of the treated silver nanoparticles is 5-20m². 2 / g.
[0008] A further improvement is that the glass powder is a Bi2O3-B2O3-ZnO series lead-free glass powder with an average particle size of 0.5μm-3μm, wherein the mass percentage of Bi2O3:B2O3:ZnO is 40%-60%:20%-35%:10%-25%.
[0009] A further improvement is that the resin is one of ethyl cellulose and acrylic resin, the solvent is one of terpineol and diethylene glycol butyl ether acetate, and the dispersant is one of polyacrylate and polyurethane.
[0010] A further improvement is that the coupling agent is one of γ-aminopropyltriethoxysilane and vinyltrimethoxysilane, the antioxidant is one of 2,6-di-tert-butyl-p-cresol and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and the leveling agent is polyether-modified polysiloxane.
[0011] A method for preparing a low-temperature silver paste FPC conductive film for electronic cigarettes includes the following steps:
[0012] Step 1: Substrate pretreatment. Place the substrate film in a vacuum plasma cleaner for 30-90 seconds to remove surface oil and weak boundary layers.
[0013] Step 2: Coating the insulating dielectric layer. Apply the insulating dielectric slurry to the surface of the substrate and dry it in an oven at 150-180℃ for 5-15 minutes to form an insulating layer with a thickness of 5μm-20μm.
[0014] Step 3: Print low-temperature silver paste. Print the low-temperature silver paste onto the insulating layer according to the preset circuit pattern.
[0015] Step 4: Low-temperature curing and molding. Place the printed substrate in a hot air circulating oven and keep it at 180-220℃ for 10-30 minutes to allow the organic carrier to volatilize, the glass powder to soften, and the nano-silver particles to sinter into a continuous conductive network.
[0016] Step 5: Apply a protective layer. Apply a UV-curable protective coating to the surface of the conductive circuit layer and cure it by irradiation with ultraviolet light for 10-30 seconds to form a protective film with a thickness of 3-10μm.
[0017] Further improvements are made in the following ways: in step one, the cleaning conditions are 80-120W power and argon protective gas is introduced at a flow rate of 50sccm; in step two, the insulating medium slurry is coated using either spin coating or slot coating, with a spin speed of 2000rpm-5000rpm and a slot coating speed of 0.5-2m / min.
[0018] Further improvements are made in the following aspects: the printing viscosity of the low-temperature silver paste in step three is controlled at 15-40 Pa·s, and the paper is allowed to stand for 5-10 minutes after printing to eliminate air bubbles; the printing is carried out using either screen printing or inkjet printing, with a screen mesh of 150-300 mesh and a photosensitive emulsion thickness of 5μm-15μm for screen printing, and a printhead resolution of ≥300dpi for inkjet printing.
[0019] Further improvements include: in step four, the heating rate for low-temperature curing is 2-5℃ / min, followed by cooling to room temperature after curing; in step five, the ultraviolet light wavelength is 365nm, and the energy density is 600-1000mJ / cm². 2 .
[0020] The beneficial effects of this invention are: the invention effectively avoids thermal damage to the substrate by utilizing the low-temperature curing characteristics of low-temperature silver paste, thus meeting the needs of electronic cigarettes for thinner and more diverse substrates.
[0021] Nano-silver particles and lead-free glass powder work together to construct a highly continuous conductive network, ensuring excellent conductivity and interfacial bonding, while also taking into account environmental friendliness.
[0022] The optimization of organic carriers and functional additives gives the paste good printability and stability. Combined with the lamination / coating process, the preparation process is simplified and the four-layer structure is achieved. This synergistically improves the overall bending resistance, e-liquid corrosion resistance and scratch resistance of the conductive film, extending its service life and providing a highly reliable, environmentally friendly and easy-to-process conductive solution for the core components of e-cigarettes. Attached Figure Description
[0023] Figure 1 This is a cross-sectional structural diagram of the conductive film of the present invention.
[0024] Figure 2 This is a flowchart of the conductive film preparation method of the present invention. Detailed Implementation
[0025] To enhance understanding of the present invention, the present invention will be further described in detail below with reference to embodiments. These embodiments are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention.
[0026] Example 1
[0027] according to Figure 1 and Figure 2 As shown, this embodiment provides a low-temperature silver paste FPC conductive film for electronic cigarettes, comprising a substrate layer, an insulating dielectric layer, a conductive circuit layer, and a protective layer arranged sequentially from bottom to top. The conductive circuit layer is formed by curing low-temperature silver paste at a curing temperature of 180℃-220℃ and a curing time of 10-30 minutes. The low-temperature silver paste is prepared by mixing nano-silver particles, glass powder, organic carrier, and functional additives in a mass percentage ratio of 60%-80%:5%-15%:10%-25%:0.1%-3%. The organic carrier is obtained by mixing resin, solvent, and dispersant in a mass percentage ratio of 30%-50%:40%-60%:1%-5% to adjust viscosity, printability, and curing behavior. The functional additives are one or more of coupling agents, antioxidants, and leveling agents, accounting for 0.1%-1% of the total mass of the low-temperature silver paste, to optimize interfacial bonding, antioxidant properties, or leveling properties.
[0028] The substrate layer is either a polyimide film or a polyester film, with a thickness of 12.5μm-50μm. After plasma cleaning, the surface has a dyne value ≥50mN / m to enhance interlayer adhesion.
[0029] The insulating dielectric layer is one of epoxy resin coating and polyimide coating, with a thickness of 5μm-20μm, which isolates the conductive lines from the substrate and has a breakdown voltage ≥5kV / mm;
[0030] The conductive circuit layer has a line width of 50μm-500μm, a line spacing of 50μm-300μm, and a sheet resistance ≤10mΩm. 2 Low conductivity loss;
[0031] The protective layer is a UV-cured acrylic coating with a thickness of 3μm-10μm. It is scratch-resistant, resistant to smoke and oil corrosion, and has a light transmittance of ≥90%, which does not affect the optical detection of the sensor.
[0032] Nano-silver particles, acting as a conductive phase, provide high electrical conductivity. With an average particle size of 50nm-200nm, these ultrafine particles enhance sintering activity and the continuity of the conductive network. They are spherical or near-spherical in shape, with a particle size distribution D90 ≤ 300nm, preventing agglomeration and clogging of the printing screen. The surface is modified with a modifier at an adsorption amount of 0.5%-2% of the silver particle mass to improve dispersibility and interfacial compatibility. The modifier is either citric acid or polyvinylpyrrolidone. The treated nano-silver particles have a specific surface area of 5-20m². 2 / g, increases the reactive sites and reduces the sheet resistance after curing.
[0033] Glass powder serves as a binder phase, promoting the sintering of silver particles and their bonding with the substrate at low temperatures. The glass powder is a Bi2O3-B2O3-ZnO series lead-free glass powder with an average particle size of 0.5μm-3μm and a purity of ≥99.5%, reducing the impact of impurities on conductivity. Its softening temperature is 300℃-450℃, lower than the 600℃-800℃ of traditional lead glass powder, making it suitable for low-temperature curing. The mass percentage of Bi2O3:B2O3:ZnO is 40%-60%:20%-35%:10%-25%.
[0034] The mechanism of action is that it partially melts during curing at 180℃-220℃, wets the silver nanoparticles and promotes the sintering of their necks, while enhancing adhesion through chemical bonding between the glass phase and the substrate.
[0035] The resin is one of ethyl cellulose and acrylic resin, providing film-forming properties and adhesion; the solvent is one of terpineol and diethylene glycol butyl ether acetate, adjusting the viscosity to 10 Pa·s-50 Pa·s, suitable for screen printing or inkjet printing; the dispersant is one of polyacrylate and polyurethane, preventing the agglomeration of nano-silver particles and improving the stability of the slurry.
[0036] The coupling agent is one of γ-aminopropyltriethoxysilane and vinyltrimethoxysilane, which enhances the chemical bonding between the glass powder and the substrate through -Si-O- bonds; the antioxidant is one of 2,6-di-tert-butyl-p-cresol and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], which inhibits the high-temperature oxidation of silver particles; the leveling agent is polyether-modified polysiloxane, which reduces surface tension and improves coating uniformity.
[0037] A method for preparing a low-temperature silver paste FPC conductive film for electronic cigarettes includes the following steps:
[0038] Step 1: Substrate pretreatment. Place the substrate film in a vacuum plasma cleaner for 30-90 seconds to remove surface oil and weak boundary layer, thereby increasing the surface energy to above 50mN / m.
[0039] The cleaning conditions are 80-120W power, with argon protective gas introduced at a flow rate of 50 sccm.
[0040] Step 2: Coating the insulating dielectric layer. Apply the insulating dielectric slurry to the surface of the substrate and dry it in an oven at 150-180℃ for 5-15 minutes to form an insulating layer with a thickness of 5μm-20μm.
[0041] The insulating medium slurry has a solid content of 20%-40%, and the coating is carried out by either spin coating or slot coating. The spin coating speed is 2000rpm-5000rpm, and the slot coating speed is 0.5-2m / min.
[0042] Step 3: Print low-temperature silver paste. Print the low-temperature silver paste onto the insulating layer according to the preset circuit pattern.
[0043] The printing viscosity of the low-temperature silver paste is controlled at 15-40 Pa·s, which is adjusted by the solvent ratio in the organic carrier. After printing, the paste is left to stand for 5-10 minutes to eliminate air bubbles. The printing process uses either screen printing or inkjet printing. For screen printing, the screen mesh count is 150-300 mesh and the photosensitive emulsion thickness is 5μm-15μm. For inkjet printing, the printhead resolution is ≥300dpi.
[0044] Step 4: Low-temperature curing and molding. Place the printed substrate in a hot air circulating oven and keep it at 180-220℃ for 10-30 minutes to allow the organic carrier to volatilize, the glass powder to soften, and the nano-silver particles to sinter into a continuous conductive network.
[0045] The heating rate for low-temperature curing is 2-5℃ / min to prevent the silver paste from cracking due to sudden heating. After curing, it is cooled to room temperature.
[0046] Step 5: Apply a protective layer. Apply a UV-curable protective coating with a viscosity of 50cps-200cps to the surface of the conductive circuit layer. Cure the coating by irradiating it with ultraviolet light for 10-30 seconds to form a protective film with a thickness of 3-10μm.
[0047] Ultraviolet light has a wavelength of 365 nm and an energy density of 600-1000 mJ / cm². 2 .
[0048] Example 2
[0049] I. Preparation of Low-Temperature Silver Paste
[0050] A low-temperature silver paste was prepared by mixing 70 wt% nano-silver particles, 10 wt% Bi2O3-B2O3-ZnO glass powder, 19 wt% organic carrier, and 1 wt% functional additives. The nano-silver particles were obtained by citric acid modification. The mass percentage of Bi2O3:B2O3:ZnO in the glass powder was 60:25:15. The organic carrier consisted of 15 wt% ethyl cellulose, 12 wt% terpineol, and 3 wt% polyacrylates. The functional additives consisted of 0.5% γ-aminopropyltriethoxysilane and 0.5 wt% 2,6-di-tert-butyl-p-cresol.
[0051] II. Preparation of Conductive Films
[0052] A 25μm thick polyimide film was plasma cleaned for 60s at 100W power, and the surface energy reached 55mN / m.
[0053] An epoxy resin insulating slurry with a solid content of 30% was spin-coated and dried at 150°C for 10 minutes to form a 10μm thick insulating dielectric layer.
[0054] The silver paste was printed into serpentine lines with a line width of 100μm and a spacing of 100μm using a 200-mesh screen printing plate.
[0055] Then it is placed in a 200℃ oven to cure for 20 minutes to form a conductive circuit layer;
[0056] Finally, a 5μm thick UV-cured acrylic coating is applied, followed by an energy treatment of 800mJ / cm². 2 The FPC conductive film is obtained by curing it with ultraviolet light with a wavelength of 365nm.
[0057] Performance testing: The sheet resistance of the conductive film was measured to be 8.2 mΩm. 2 It has an adhesion rating of 4B, a bending resistance of 5200 cycles, and a sheet resistance change rate of <5% after aging at 180℃ for 24 hours.
[0058] Comparative Example
[0059] A conventional conductive film was prepared by curing a mixture of 65% silver nanoparticles, 25% PbO-B2O3 glass powder, and 10% organic carrier. The PbO:B2O3 mass percentage in the glass powder was 60:40. The organic carrier consisted of 45% resin, 50% diethylene glycol monobutyl ether, and 5% lecithin dispersant. The film was cured at 280°C for 15 minutes. The film exhibited the following properties: a sheet resistance of 12 mΩm. 2 It can withstand 1500 flexural cycles, and the sheet resistance change rate is >15% after aging at 180℃ for 24 hours. After curing, the polyimide film substrate shows obvious shrinkage with a shrinkage rate >2%.
[0060] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A low-temperature silver paste FPC conductive film for electronic cigarettes, characterized in that: The product comprises, from bottom to top, a substrate layer, an insulating dielectric layer, a conductive circuit layer, and a protective layer. The conductive circuit layer is formed by curing low-temperature silver paste. The low-temperature silver paste is prepared by mixing nano-silver particles, glass powder, organic carrier, and functional additives in a mass percentage ratio of 60%-80%:5%-15%:10%-25%:0.1%-3%. The organic carrier is prepared by mixing resin, solvent, and dispersant in a mass percentage ratio of 30%-50%:40%-60%:1%-5%. The functional additives are one or more of coupling agents, antioxidants, and leveling agents. The silver nanoparticles have an average particle size of 50nm-200nm and their surface is modified with a modifier containing 0.5%-2% of the silver particle mass. The modifier is either citric acid or polyvinylpyrrolidone. The treated silver nanoparticles have a specific surface area of 5-20m². 2 / g; The resin is one of ethyl cellulose and acrylic resin, the solvent is one of terpineol and diethylene glycol butyl ether acetate, and the dispersant is one of polyacrylate and polyurethane. The coupling agent is one of γ-aminopropyltriethoxysilane and vinyltrimethoxysilane, the antioxidant is one of 2,6-di-tert-butyl-p-cresol and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and the leveling agent is polyether-modified polysiloxane. The glass powder and nano-silver particles are sintered at 180-220℃ to form a continuous conductive network.
2. The low-temperature silver paste FPC conductive film for electronic cigarettes according to claim 1, characterized in that: The substrate layer is one of polyimide film and polyester film, with a thickness of 12.5μm-50μm; the insulating dielectric layer is one of epoxy resin coating and polyimide coating, with a thickness of 5μm-20μm; the conductive circuit layer has a line width of 50μm-500μm and a line spacing of 50μm-300μm; the protective layer is a UV-cured acrylate coating with a thickness of 3μm-10μm.
3. The low-temperature silver paste FPC conductive film for electronic cigarettes according to claim 1, characterized in that: The glass powder is a Bi2O3-B2O3-ZnO series lead-free glass powder with an average particle size of 0.5μm-3μm, wherein the mass percentage of Bi2O3:B2O3:ZnO is 40%-60%:20%-35%:10%-25%.
4. A method for preparing a low-temperature silver paste FPC conductive film for electronic cigarettes according to any one of claims 1-3, characterized in that, Includes the following steps: Step 1: Substrate pretreatment. Place the substrate film in a vacuum plasma cleaner for 30-90 seconds to remove surface oil and weak boundary layers. Step 2: Coating the insulating dielectric layer. Apply the insulating dielectric slurry to the surface of the substrate and dry it in an oven at 150-180℃ for 5-15 minutes to form an insulating layer with a thickness of 5μm-20μm. Step 3: Print low-temperature silver paste. Print the low-temperature silver paste onto the insulating layer according to the preset circuit pattern. Step 4: Low-temperature curing and molding. Place the printed substrate in a hot air circulating oven and keep it at 180-220℃ for 10-30 minutes to allow the organic carrier to volatilize, the glass powder to soften, and the nano-silver particles to sinter into a continuous conductive network. Step 5: Apply a protective layer. Apply a UV-curable protective coating to the surface of the conductive circuit layer and cure it by irradiation with ultraviolet light for 10-30 seconds to form a protective film with a thickness of 3-10μm.
5. The method for preparing a low-temperature silver paste FPC conductive film for electronic cigarettes according to claim 4, characterized in that: In step one, the cleaning conditions are 80-120W power and argon protective gas is introduced at a flow rate of 50sccm. In step two, the insulating medium slurry is coated using either spin coating or slot coating. When spin coating, the rotation speed is 2000rpm-5000rpm, and when slot coating, the coating speed is 0.5-2m / min.
6. The method for preparing a low-temperature silver paste FPC conductive film for electronic cigarettes according to claim 4, characterized in that: In step three, the printing viscosity of the low-temperature silver paste is controlled at 15-40 Pa·s, and after printing, it is allowed to stand for 5-10 minutes to eliminate air bubbles. The printing is carried out using either screen printing or inkjet printing. For screen printing, the screen mesh number is 150-300 mesh and the photosensitive emulsion thickness is 5μm-15μm. For inkjet printing, the printhead resolution is ≥300dpi.
7. The method for preparing a low-temperature silver paste FPC conductive film for electronic cigarettes according to claim 4, characterized in that: In step four, the heating rate for low-temperature curing is 2-5℃ / min, and the material is cooled to room temperature after curing. In step five, the ultraviolet light wavelength is 365nm, and the energy density is 600-1000mJ / cm². 2 .
Citation Information
Patent Citations
Low-temperature sintered nano silver paste and sealing method of sealing device
CN110429065A
Flexible circuit board made of weldable low-temperature silver paste and preparation process of flexible circuit board
CN120692753A
